Dignity and human life: two fundamental concepts of medical ethics - Carrasco de Paula, Ignazio (Medicina e Morale, 1995)
The article begins with the observation regarding the present difficulty in constructing a common ethical plan for man, also because of the ambiguity that arises from the meanings given to words, and it aims to analyse the sense and the meaning of the terms human life and dignity. After a historical examination of the meaning attributed to the word fife in pre-Christian, Christian and post-Cartesian times, the author argues that the life is something more than what it appears to be and that this is possible thanks to two other properties that make up the human person: integrity and identity. The first term is defined as the way one refers to natural, harmonious and synergic wholeness, while the second term includes pertinacity in being oneself as one develops in time. If integrity and identity are part of what makes up the person, then any attempt to destroy them is like the demolition of man himself. The main principles of Bioethics are thus defined: 1. the respect of the inviolability of human life; 2. the respect for its integrity. As far as the word dignity is concerned, this is referred to as something or someone who by his/its nature possesses virtues, nobility, excellence. When referred to man, the term indicates a value that can not be compared with other values. That is, man does not have a price because be himself is the measure of value far all things. Affirming the dignity of human life means recognizing the unique value of man as an individuai an d concrete living person.